Pembangunan Kereta Cepat Jakarta-Bandung: Memaknai Konsultasi Publik dan Partisipasi Masyarakat dalam Pengadaan Tanah - Androvaga Renandra Tetama; Suharno Suharno; Yaritza Nafa Tyola (Widya Bhumi, 2022)
The Jakarta Bandung Fast Train (KCJB) infrastructure development aims to improve mass transportation performance. The KCJB construction work, however, was hampered by the lengthy and expensive process of financing land acquisition. The purpose of this article is to describe the achievement of KCJB development targets and to explain why it is critical to implement meaningful public consultation and community participation (KPPM) in land acquisition. Through a review of the literature, this study employs the descriptive qualitative method. According to the study's findings, the Indonesian and Chinese governments are committed to completing the KCJB's construction. Despite the fact that the land acquisition activities lasted five years (2017-2021), they were able to provide land with an area of 7.6 million square meters and a length of 142.3 km. The lengthy land acquisition process has resulted in an increase in land acquisition financing from two trillion to 113 trillion. Project construction work has reached 88.8 percent completion by the end of 2022. This study emphasizes the importance of KPPM in preventing conflict or rejection, social disintegration, or even violence, all of which result in the failure to meet KCJB's development targets on time. To improve the performance of the mass transportation sector, the two countries must complete construction of the KCJB as soon as possible. Pembangunan infrastruktur Kereta Cepat Jakarta Bandung (KCJB) bertujuan untuk pengembangan kinerja transportasi massal. Namun, pekerjaan pembangunan KCJB terganjal oleh lama dan mahalnya pembiayaan pengadaan tanah. Artikel ini bertujuan untuk menguraikan pencapaian target-target pembangunan KCJB dan memaparkan urgensi penerapan konsultasi publik dan partisipasi masyarakat (KPPM) yang bermakna dalam pengadaan tanah. Penelitian ini menggunakan metode kualitatif deskriptif melalui studi pustaka. Hasil penelitian menyebutkan bahwa pemerintah Indonesia-Cina berkomitmen menyelesaikan pembangunan KCJB. Meskipun pengadaan tanah berlangsung selama lima tahun (2017-2021), kegiatan tersebut mampu menyediakan tanah seluas 7,6 juta meter persegi dengan panjang 142,3 km. Lamanya proses pengadaan tanah berdampak pada meningkatnya pembiayaan pengadaan tanah dari perencanaan awal dua triliun menjadi 113 triliun. Hingga akhir 2022 pekerjaan konstruksi proyek mencapai 88,8 persen. Kajian ini menekankan pentingnya KPPM untuk mencegah terjadinya konflik atau penolakan, disintegrasi sosial, atau pun kekerasan yang berdampak tidak tercapainya target-target pembangunan KCJB dengan tepat waktu. Kedua negara harus segera menyelesaikan pembangunan KCJB untuk meningkatkan kinerja sektor transportasi massal.